PUBLIC AUTHORITY AND STATE LEGAL REGIME - Олейников, Сергей (SWorldJournal, 2021)
Abstract. The state-legal regime investigated as an integral part of the political regime of society, in which the public power, having a legal nature, receives the grounds for its legitimacy. The political regime manifests its specificity in the degree